2009
DOI: 10.1111/j.1365-2745.2009.01492.x
|View full text |Cite
|
Sign up to set email alerts
|

Density‐dependence at multiple scales in experimental and natural plant populations

Abstract: Summary 1.The survival and reproduction of individual plants may be related to the distribution of conspecific neighbours with which they interact. 2. We used 2 years' data from a field experiment to relate the reproduction and survival of focal Silene latifolia plants to the numbers of conspecific plants and flowers within a range of distances (0.16-150 m) from the focal plants. Thus we consider spatial scale as a continuously-varying component of population density. 3. Because the data come from a single con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 68 publications
0
39
0
2
Order By: Relevance
“…The differences between sites appear to be robust if one considers that our lack of knowledge regarding several parameters (pollinator species composition, age, sex, experience of individuals) introduced potential variance in our data that would favour the null hypothesis that no differences exist. While the majority of studies have observed that the density of flowering species can be positively correlated with pollinator visitation rates and plant reproductive success (Gunton and Kunin 2009;Kunin 1993Kunin , 1997Sih and Baltus 1987;Sun et al 2010), so far no one has explicitly focussed on the phenotypic plasticity of pollinator foraging behaviour facing cheaters derived from a rewarding species in dense and sparse populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences between sites appear to be robust if one considers that our lack of knowledge regarding several parameters (pollinator species composition, age, sex, experience of individuals) introduced potential variance in our data that would favour the null hypothesis that no differences exist. While the majority of studies have observed that the density of flowering species can be positively correlated with pollinator visitation rates and plant reproductive success (Gunton and Kunin 2009;Kunin 1993Kunin , 1997Sih and Baltus 1987;Sun et al 2010), so far no one has explicitly focussed on the phenotypic plasticity of pollinator foraging behaviour facing cheaters derived from a rewarding species in dense and sparse populations.…”
Section: Discussionmentioning
confidence: 99%
“…Plant populations/communities with higher densities generally attract a larger number of pollinators and have a higher reproductive output than lower densities (Bernhardt et al 2008;Gunton and Kunin 2009;Kunin 1997). Large floral aggregations supposedly emit more olfactory and visual cues to attract pollinators (Shao et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Por outro lado, a maior densidade de plântulas, devido ao microambiente favorável, parece determinar valores mais altos de mortalidade, resultada de controle populacional denso-dependente, como o observado para na clareira B (GUNTON & KUNIN, 2009). No entanto, apesar do crescimento populacional diferenciado, em ambas as clareiras estudadas, registrou-se efetiva capacidade de produção e manutenção de estoque de plântulas de M. skvortzovii, promovendo a sua permanência na área.…”
Section: Resultsunclassified
“…A lack of these feedbacks in the responses of species to density is termed neutral density dependence and logically leads to the broader scope of ecological inquiry in plants and animals whether regulation or limitation is determining the relative abundance of a given species (White 2001). Regulation is best defined as the direct effects of other species (or intra-specific interactions) which reduce the numbers of a species below the capacity of the environment-sometimes called boundedness (Gunton and Kunin 2009;Hixon et al 2002;White 2001). Limitation is the capacity of environment to support a certain number of individuals (White 2001).…”
Section: Fundamental Plant Ecology Concepts and Invasionmentioning
confidence: 99%
“…This 'mean field' or neighbourhood-level approach to species density (Gunton and Kunin 2009) can also be scaled up to community-level manipulations (Goldberg et al 2001;Lortie and Turkington 2002) whereby the total number of individuals for all species is increased. At both scales, population dynamics are inferred by comparing changing germination, recruitment, survival, etc.…”
Section: Fundamental Plant Ecology Concepts and Invasionmentioning
confidence: 99%